Would market sheds improve market participation and earnings of small ruminant keepers? Evidence from Ethiopia - Zeleke, F.; Kassie, Girma T.; Haji, J.; Legesse, B. (Wiley, 2021)
Livestock markets and marketing are crucial components of the agricultural transformation agenda in Ethiopia. There is, however, little or no scientific evidence for the demand for livestock market facilities to guide the national effort. Using panel data, we estimate the effect of livestock market shed provision on market participation and revenue from small ruminants in Central Ethiopia. Experimental market sheds were constructed in nine markets, with baseline and follow‐up surveys conducted with a sample of 50 marketers from each of 16 markets. We employ different formulations of a difference‐in‐differences (DiD) model, including a combined estimation with propensity score matching. Our results show that provision of market sheds significantly increase farmers’ earnings from small ruminant sales. DiD estimated with a matched sample also shows that market participation increased among smallholder farmers close to the markets with sheds. Our findings support the investment in market facilities in the central highlands and other comparable socio‐economic settings in Ethiopia.